(untitled) (Eurasian Journal of Ecology, 2016)
The hypothesis on the ancient Central Eurasian origin of the carmine industry was discussed, the potential sources for ancient and medieval dyers probably were Porphyrophora sophorae, P. violaceae, P. cynodontis, P. arnebiae, P. odorata. Among the post-soviet states the Kazakhstan, Armenia, Uzbekistan, Tajikistan, Turkmenistan, Russia and Ukraine have a big resource for carmine production. There are P. polonica in Europe, P. vilossa in Russian Far East, P. hamelii in Armenia, and P. polonica, P. sophorae, P. gigantea and P. victoriae in Kazakhstan. Also Porphyrophora species could be used in medicine and archaeology.